KEWENANGAN PENGELOLAAN WISATA BAHARI OLEH PEMERINTAH DESA DI KABUPATEN BADUNG (SUATU STUDI PENGELOLAAN WISATA BAHARI DI DESA PECATU) - Ariek Dwijaya, Kadek; Arya Utama, I Made; Dyah Satyawati, Ni Gusti Ayu (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014, 2014)
One of local authority of central government which is delegated to the village shall be tourism affairs. Pecatu Village has numerous marine tourism destinations. Pecatu Village is affirmed as marine tourism area as it is supported by its natural potential of the sea. Thus, local government is expected to conduct a strategic effort that the community can benefit from the development of the tourism sector in the region of Pecatu Village. This paper aims to understand and comprehend concerning marine tourism management authority by the government in the Pecatu village and also to identify supporting factors and obstacles in the management of marine tourism in the Village of Pecatu. This paper applies empirical methods of judicial writing. Rural authority in the management of marine tourism shall include : Management of tourist attraction in the village excluding from the tourism master plan, management of recreation and public entertainment places in the village, recommendation on issuance of licenses of cottage in the urban tourism sector. Implementation of the management of marine tourism in the Village of Pecatu shall be influenced by supporting factors from both internal and external aspects, and there are also the obstacles in the implementation of the management itself.
Keywords: Authority , marine tourism , village